PENDEKATAN PAILKEM MENINGKATKAN MINAT BELAJAR IPA SISWA SEKOLAH DASAR - Murniati Murniati; Arsad Bahri; Evi Ristiana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to see the effect of PAILKEM approach towards students’ science learning interest at grade IV elementary schools of Cluster 1 Kecamatan Bontomarannu. This research was conducted at SDI Songkolo by using a quasi-experimental method of the non-equivalent control group type. The data were collected through a questionnaire of science learning interest. The results showed that PAILKEM had a positive effect on students' science learning interest. This was proved by the mean score of the posttest in the experimental class which was 4.13, compared to the score in the control class which was 3.89. This was also supported by the result of hypothesis test showing that tcalculated > ttable (14.91 > 2.007).